2020
DOI: 10.3762/bjnano.11.149
|View full text |Cite
|
Sign up to set email alerts
|

The influence of an interfacial hBN layer on the fluorescence of an organic molecule

Abstract: We investigated the ability of a single layer of hexagonal boron nitride (hBN) to decouple the excited state of the organic molecule 3,4,9,10-perylene tetracarboxylic dianhydride (PTCDA) from the supporting Cu(111) surface by Raman and fluorescence (FL) spectroscopy. The Raman fingerprint-type spectrum of PTCDA served as a monitor for the presence of molecules on the surface. Several broad and weak FL lines between 18,150 and 18,450 cm−1 can be detected, already from the first monolayer onward. In contrast, FL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 78 publications
(168 reference statements)
0
9
0
Order By: Relevance
“…In particular, we focus our study on the RET as well as on the nonradiative and radiative de-excitation owing to the electromagnetic interactions discussed below and on their evolution with the thickness of the ionic crystal layer introduced between the molecule and the substrate. To this end, we choose a representative system with an energy-level alignment shown in Figure a as considered in numerous experimental and theoretical works. ,,,,,, …”
Section: Excited-state Decaymentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, we focus our study on the RET as well as on the nonradiative and radiative de-excitation owing to the electromagnetic interactions discussed below and on their evolution with the thickness of the ionic crystal layer introduced between the molecule and the substrate. To this end, we choose a representative system with an energy-level alignment shown in Figure a as considered in numerous experimental and theoretical works. ,,,,,, …”
Section: Excited-state Decaymentioning
confidence: 99%
“…Along with RET, the decay of the excited state can also involve the intramolecular de-excitation via an excited-state → ground-state transition with photon emission (radiative decay, rate Γ R ) or with nonradiative excitation transfer to the substrate also identified as ohmic losses (nonradiative de-excitation, rate Γ NR ). ,, A quantum treatment incorporating the nonlocality of the metal response ,, can be more adequate to describe these processes when the molecule is adsorbed directly at the metal surface. However, the presence of the spacer layer between the emitter and the metal surface reduces the effect of nonlocality and allows us to use classical local electrodynamics to properly estimate these two decay channels, as determined by the electromagnetic interactions between the adsorbate and the substrate. ,, …”
Section: Excited-state Decaymentioning
confidence: 99%
See 1 more Smart Citation
“…The minor spectral features at short wavelengths are surface-enhanced Raman bands of PTCDA. 18,19,37 The three dominant emission bands are assigned to excimer states (E), CT excitons (CT), and Frenkel excitons (FE) in concordance with our earlier TRPL study. 18 In this study, different dynamics of the three excitonic states have been observed: the lifetimes of the CT excitons and the excimers strongly increase with increasing film thickness from picoseconds to nanoseconds, while the Frenkel excitons, independent of the thickness, decay on an ultrafast time scale below the time resolution of the TRPL experiment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Schaal et al [ 86 ] showed that h BN on Ni(111) electronically decoupled tetraphenyldibenzoperiflanthene such that the molecular vibronic progression was observable by in situ differential reflectance spectroscopy, which is otherwise only achieved for multilayers on the bare Ni. On h BN/Cu(111), Zimmermann et al [ 87 ] could visualize the molecular orbitals of pyrene derivatives by STM at the submolecular level, while Brülke et al [ 88 ] measured the fluorescence of monolayer perylenetetracarboxylic dianhydride (PTCDA), which is quenched on bare Cu(111) and would require three molecular decoupling layers to be probed on Cu(111). In all three studies using h BN, ordered molecular films were observed.…”
mentioning
confidence: 99%